Respon Pertumbuhan Tanaman Junggul (Crassocephalum crepidioides) terhadap Pemberian Berbagai Jenis Pupuk Kandang dan Kosentrasi Boron - saniman saniman; Mahayu Woro Lestari; Sugiarto Sugiarto; Siti Asmaniyah (Folium : Jurnal Ilmu Pertanian, 2019)
One of the medicinal plants known to the public is the superior plant (crassocephalum crepidioides). This plant is a shrub that grows wild in the tropics and sub-tropics. The aim of the study was to determine the interaction between the type of manure and the concentration of boron and the effect of manure and boron concentration on the growth and quality of crassocephalum crepidioides. The method used is factorial Randomized Block Design (RBD). Factor 1 is manure namely Po = No Fertilizer, P1 = Chicken Manure 50 gr/Polybag, P2 = Goat Manure 50 gr/Polybag and P3 = Cow Manure 50 gr/Polybaq. The recommended dosage used is 20 tons / ha. Factor 2 is giving Boron namely Bo = No Boron, B1 = 50 ppm / L, B2 = 100 ppm / L and B3 = 150 ppm/L. Analysis of variance (Test F) with a level of 5% and a follow-up test with Honest Real Difference (BNJ) level of 5%. The results of the type of cow manure (P3) gave a significant effect on the number of branches (8.11 branches), leaf area (1810.08 cm2), and trimmed dry weight of tanman (9.57 g) for cow manure (P3) and ( 6.27 g) for goat manure (P3). The treatment of giving Boron does not show a significant difference in the growth and yield of juntung plants.